Toward greater access and impact: Directions for a sociological understanding of Philippine higher education - Leviste, Enrique Niño P (Archīum Ateneo, 2020)
In the Philippines and many other developing countries higher education has a special function, not only with regard to educating students for jobs but also with regard to partnerships for industry growth, research for national development and the formation of critical leaders in society. However, these aims are impeded by issues of access and the unclear impact of higher education and society on each other. In this conceptual study, the authors highlight four directions for a sociological analysis of Philippine higher education: students’ access to higher education, its organization and whether it promotes or impedes access, institutions’ responses to social, economic and technological changes, and their active influence on society. By reviewing and organizing different frameworks and empirical studies, the authors suggest ways of understanding higher education in the Philippines and how a sociological perspective can clarify postsecondary institutions’ role in promoting access for students and having a greater impact on society. Having this sociological consciousness can help administrators, instructors, students and industry leaders to be aware of how higher education in developing contexts can be leveraged for societal development.